Assessment of the influence of weather conditions and the protection system on the development of harmful organisms in the Western Forest zone - Snizhok, O.; Pershuta , V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To study the influence of weather conditions and protection system on the species composition of pests on sunflower crops in the Western Polissya region.Methods. Visual — to determine the phenological phases of growth and development of the crop; counting — to determine the development of diseases, pests, parameters of the crop structure and crop yield; chemical — to determine the content of nutrients in the soil; mathematical and statistical — to assess the reliability of the research results.Results. It was found that in the sunflower agrocenosis, weather conditions and the protection system have a significant impact on the species composition of pests in the Western Polissya region. It was found that climate change (the average annual air temperature in Ukraine has increased by more than 0.9°C over the past century) and the creation of new early-ripening sunflower varieties and hybrids have led to favorable conditions for growing the crop in the Western regions. The analysis of statistical data showed that the area under sunflower in Rivne region increased from 3 thou hectares in 2015 to 49 thou hectares in 2023, and in Volyn region — from 2 to 41.8 thou hectares. However, these regions are subject to fluctuating weather conditions, with heavy short-term rains alternating with drought. Violations of agricultural practices also contribute to the problem. These factors lead to an increase in pathogenic infections and the number of weeds. Studies have shown that the species composition and development of diseases and weeds are directly dependent on weather conditions. In 2022, the average daily air temperature was 11.1°C, which is 2.0°C lower than long-term data, and there was 49.6 mm of precipitation (the climatic norm is 24 mm). Such weather conditions significantly slowed down the development of sunflower and contributed to a high density of weeds (816.0 plants/m2). In 2021 and 2023, the number of weeds did not exceed 487 units/m2. During the growing season, the optimum air temperature (19.8°C) and frequent precipitation (283.8 mm of precipitation) in 2022 caused a significant development of septoria (30.2—32.4%) and white rot on sunflower stems (28.0—35.0%) in variants without fungicides, and the development on baskets was 59.0—65.0%.Conclusions. In the Western Polissya zone, the most common weeds during (2021—2023) were common spurge (Echinochloa crus-galli L.), wild violet (Viola arvensis Murr.), common bindweed (Amaranthus retroflexus L.), white quinoa (Chenopodium album L.), bindweed (Polygonum convolvulus L.), pink thistle (Cirsium arvense L.), medium starthistle (Polygonum convolvulus L.), rape stubble (Brassica napus L.), common shepherd’s purse (Capsella bursa-pastoris L.); diseases — Septoria helianthi Ell. and white rot (Sclerotinia sclerotiorum Lib.).